Integrating Male Technologists Into Mammography: Overcoming Gendered Barriers Through Policy and Education. - Mohammed, Sharon; Gomez, Dominique; Slinger, Vilma; Taylor, Natasha; Benka-Coker, Amelia (Radiologic Science & Education, 2025)
This literature review explored the exclusion of male technologists from mammography by examining key themes related to gender, professional identity, and healthcare delivery. A comprehensive search conducted through New York University Langone Health's Research Medical Library identified evidence-based integration strategies, including structured mentorship, targeted patient education, and institutional support mechanisms. Across the literature, four foundational themes emerged: professional identity formation, cultural competency, organizational integration, and stereotype management. Patient-centered approaches, such as transparent communication protocols and the routine availability of chaperones, were shown to improve patient comfort and acceptance. Successfully integrating male technologists into mammography requires addressing systemic barriers through inclusive policies, engaged leadership, and culturally responsive practices. These strategies not only promote gender equity within the imaging workforce but also enhance patient care and organizational effectiveness.